NUCLEAR MINERALS IN PAKISTAN - Mansoor, Muhammad (The Nucleus, 2020)
Strategic importance of Nuclear Minerals was recognized during early formative years of the Pakistan Atomic Energy Commission, and prospecting for uranium was started in Dera Ghazi Khan in collaboration with the Geological Survey of Pakistan (GSP) as early as 1961. Later, the responsibility for countrywide surveys and exploration was fully entrusted with PAEC and in this respect a Directorate of Nuclear Minerals(DNM) was established in 1966 at Lahore. Later, DNM was shifted to the Atomic Energy Centre (AEC), Lahore building and renamed as Atomic Energy Minerals Centre. It has state-of-the-art Chemistry, Mineralogy, Remote Sensing and Electronics Laboratories and an Ore Processing Pilot Plant. The Centre has Prospecting, Exploration, Geophysics, Geochemistry, Geo-tectonics, Mining and Drilling Sections. Regional Offices have been established to facilitate work at Karachi, Quetta and Peshawar. Siwaliks were recognized as a favourable geological formation of prime importance. Sandstone-shale sequence of Siwaliks Formation is exposed in all provinces of Pakistan and in Azad Jammu and Kashmir (AJK), broadly categorized into Rajanpur-Dera Ghazi Khan, Bannu Basin-Kohat Plateau and Potwar-AJK zones. Baghalchur, Nangar Nai and Taunsa uranium deposits have been discovered in the Rajanpur- D.G.Khan Zone. Qabul Khel and Shanawah Uranium deposits have been discovered in the Shanawah- Kohat Plateau Zone. Prospection and exploration is in progress. The first uranium mine was opened at Baghalchur, and uranium mill was established at D.G Khan in 1977-78 all by indigenous effort. The uranium mine was the most advanced and mechanized mine of that time in the country. Later, a second uranium mine was opened at Qabul Khel in 1992, which was based on a new and advanced in situ leach technology, developed to suit local geological and ore zone parameters. Mining of Nanganai and Taunsa Deposits was started respectively in 1996 and 2002, and is also based on in situ leach technology which is low cost and environment friendly.